Evaluating surrogate correlation models and iodinated haloacetic acid formation of iodinated contrast media after LPUV/Cl2, LPUV/NH2Cl, and LPUV/H2O2. Issue 4 (August 2021) - Lopez-Prieto, Israel J.; Daniels, Kevin D.; Wu, Shimin; Snyder, Shane A.
Abstract: Iodinated X-ray contrast media (ICM) are a class of pharmaceuticals that are ubiquitously found at trace levels (µg/L) in wastewater, surface water, groundwater, and drinking water. Due to their polar features, they are not effectively removed during conventional water treatment and provide an iodine source for the formation of iodinated-disinfection by-products (I-DBPs) during disinfection. This work examined the suitability of organic parameters (i.e. total organic carbon (TOC), ultraviolet absorbance (UVA254 ), total fluorescence (TF) and specific ultraviolet absorbance (SUVA)), as surrogate correlation models to estimate the removal of seven target ICMs. Three advanced oxidation processes (AOPs), LPUV/H2 O2, LPUV/Cl2 and LPUV/NH2 Cl, were applied to develop the surrogate correlation models. Pearson correlation coefficients were compared with linear correlation models to determine the ideal surrogate parameter for each model type. The formation of iodinated-haloacetic acids (I-HAAs) were also monitored for each AOP treatment. Results did not show any significant differences for ICM attenuation across the AOP treatments, illustrating UV photolysis is the main driving force to attenuate ICMs. Surrogate correlation models demonstrated a good correlation (R 2 = 0.8211 and 0.7887) and strong Pearson correlation (R = 0.9602 and 0.8881) for UVA254 during LPUV/Cl2 and LPUV/H2 O2 treatment. Additionally, two I-HAA, monoidoacetic acid (MIAA) and bromoiodoacetic acid (BIAA), were detected (up to 2.4 µg/L) after LPUV/Cl2 and LPUV/NH2 Cl AOP treatment. Graphical Abstract: ga1 Highlights: ICM abatement during UV photolysis was not enhanced with the addition of oxidants. ICM attenuation during LPUV/H2 O2 treatment was effectively predicted with linear surrogate correlation models. Sub-ppb I-HAAs were formed from chlorinated oxidants during ICMs photolysis. Two I-HAAs were detected after LPUV/Cl2 and LPUV/NH2 Cl treatment.